2016
DOI: 10.1021/acs.orglett.6b03394
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed α-Arylation of Vinylogous Esters for the Synthesis of γ,γ-Disubstituted Cyclohexenones

Abstract: A palladium-catalyzed α-arylation of cyclic vinylogous esters to form products that are converted in one step to γ-alkyl-γ-aryl-substituted cyclohexenones is reported. This Pd-catalyzed reaction proceeds at room temperature, is generally high-yielding, and uses an amount of a commercially available catalyst as low as 0.25 mol %. The scope of aryl bromides is particularly broad, and alkenyl bromides can also be used. This two-step protocol, comprising α-arylation and reductive transposition, can be performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Subjecting 13 to 12.5 mol-% nitro-Grela catalyst in refluxing toluene for 27 h provided in 53 % yield the TBS-protected 5-phenyl-3-isopropyl-4-methylenecyclohex-2-en-1-ol 16. [38] Next, we implemented a Pd-catalyzed α-arylation, recently reported by Lautens and co-workers, [38] to transform the 3-ethoxy-5-methylcyclopent-2-en-1-one (21) into the corresponding 5-methyl-5-phenyl-substituted ethoxy cyclopentenone 22. Instead of first reacting with the vinyl group of 13, the Grela catalyst 14 forms the ruthenium carbene 15, which then closes to a 6-membered ring with the vinyl carbinol substituent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subjecting 13 to 12.5 mol-% nitro-Grela catalyst in refluxing toluene for 27 h provided in 53 % yield the TBS-protected 5-phenyl-3-isopropyl-4-methylenecyclohex-2-en-1-ol 16. [38] Next, we implemented a Pd-catalyzed α-arylation, recently reported by Lautens and co-workers, [38] to transform the 3-ethoxy-5-methylcyclopent-2-en-1-one (21) into the corresponding 5-methyl-5-phenyl-substituted ethoxy cyclopentenone 22. Instead of first reacting with the vinyl group of 13, the Grela catalyst 14 forms the ruthenium carbene 15, which then closes to a 6-membered ring with the vinyl carbinol substituent.…”
Section: Resultsmentioning
confidence: 99%
“…Unless otherwise stated, reagents and solvents (puriss. [38] At room temp., EtOH (48 mL) was added to a suspension of cyclopentane-1,3-dione (20; 10.0 g, 102 mmol, 1.00 eq.) Purification of the reaction products was carried out on a Biotage Isolera One Spektra System with an Accelerated Chromatographic Isolation (ACI) using SNAP Ultra (Ultra-Fast Flash Chromatography) Cartridges packed with HP-Sphere spherical silica, 25 μm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In which, cyclic vinylogous ester (3-or β-alkoxyl substituted cyclic α, β-unsaturated ketone) is more electron-rich thereby its dienolate is hardly formed by deprotonation. Furthermore, the dienolates are easy to polymerize with itself, further To overcome the limitation of aryl sources in this reaction, Lautens et al screened different palladium catalysts, and finally found that products (83a-83f) could be generated with high yield using the Palladium precatalyst Pd-P(tBu) 3 -G2, and α′ arylation could be realized at room temperature (Scheme 31) [82]. The α′-arylation of 3-ethoxy-2-cyclohexenone can also be effectively promoted by using the bulky base [83] or phosphine ligand with large steric hindrance [84].…”
Section: Palladium-catalyzed Intramolecular α-C(sp 3 )-H Arylations Of Cyclic Carbonyl Compoundsmentioning
confidence: 99%